2015
DOI: 10.1007/s00411-015-0621-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cell response to low doses of photon irradiation—Part 1: on the origin of fluctuations

Abstract: Intra- and inter-individual variability is a well-known aspect of biological responses of cells observed at low doses of radiation, whichever the phenomenon considered (adaptive response, bystander effects, genomic instability, etc.). There is growing evidence that low-dose phenomena are related to cell mechanisms other than DNA damage and misrepair, meaning that other cellular structures may play a crucial role. Therefore, in this study, a series of calculations at low doses was carried out to study the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this sense, starting from concepts of the existing models, such as the notion of local and sublethal events, we resorted to microdosimetry and nanodosimetry to implement a fully statistical methodology. Indeed, the magnitude of fluctuations in energy deposition at micrometric and nanometric scales is not negligible and cannot be disregarded (Cunha et al 2016b). With NanOx, it is also possible to obtain the α and β coefficients of the LQ model, which would allow for the implementation of the model in a TPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, starting from concepts of the existing models, such as the notion of local and sublethal events, we resorted to microdosimetry and nanodosimetry to implement a fully statistical methodology. Indeed, the magnitude of fluctuations in energy deposition at micrometric and nanometric scales is not negligible and cannot be disregarded (Cunha et al 2016b). With NanOx, it is also possible to obtain the α and β coefficients of the LQ model, which would allow for the implementation of the model in a TPS.…”
Section: Introductionmentioning
confidence: 99%
“…where C norm is a normalization factor ensuring that the average of cell survival over all irradiation configurations leads to the experimental probability of cell survival to an irradiation with a reference radiation characterized by the coefficients α r and β r of the respective LQ fit. C norm , α G and β G are determined as a function of the α r and β r coefficients through the convolution of the cell survival for a given configuration of radiation impacts c K with a Gaussian law knowing that: (1) for an irradiation with low-LET photons, the distribution of energy depositions at a microscopic scale corresponding to that of cell dimensions can be modeled by a Gaussian law (Cunha et al 2016b); and (2) the cell survival to a given configuration c K can be determined from the specific energy Z cK in the sensitive volume, i.e.…”
mentioning
confidence: 99%
“…Thus, a new theoretical framework, called NanOx ® (41), was created gathering principles from existing approaches, while addressing some of their weaknesses (42,43). NanOx ® is a multiscale model that takes the stochastic nature of radiation at nanometric and micrometric scales fully into account, which has been shown to be drastically important (42)(43)(44). It also integrates the chemical aspects of radiation-matter interaction by means of a chemical specific energy, a new quantity determined from the production of reactive chemical species induced by irradiation (45).…”
Section: Biophysical Modelization Of Cell and Tissue Responses To Parmentioning
confidence: 99%
“…This notion was reused to describe processes leading to cell death due to energy deposition at the nanometric scale. However, as it was shown that the magnitude of fluctuations of such energy deposition cannot be disregarded [18], the local dose was replaced in NanOx by a stochastic quantity representing the physico-chemical mechanisms. This is in contrast to the latest version of the LEM [11,19], where the biological effect of ions is primarily linked to the initial distribution of DNA doublestrand breaks (DSB) induced by radiation rather than the local dose itself.…”
Section: Introductionmentioning
confidence: 99%